2017
DOI: 10.1371/journal.pone.0176092
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of a resistance vs. an aerobic single session on attention and executive functioning in adults

Abstract: Evidence from recent studies showed that acute aerobic exercise results in improvements in different cognitive functions. The goal of this study was to assess the influence of acute bouts of aerobic versus resistance exercise on attention and executive function in adults. Thirty-nine physically active adults (age = 52±8 yr) served as participants. Each participant visited the laboratory four times: on the first visit participants performed a cognitive test (NeuroTrax) followed by an aerobic fitness assessment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 48 publications
4
30
1
3
Order By: Relevance
“…It is also interesting to note that, using a similar protocol but with a mixed group of middle-aged men and women, Dunsky et al (2017) found increased scores of attention following an aerobic exercise session on a treadmill, but not after a strength session. They also found only marginally significant improvement in executive function scores following both aerobic exercise and resistance exercise sessions.…”
Section: Figurementioning
confidence: 94%
See 2 more Smart Citations
“…It is also interesting to note that, using a similar protocol but with a mixed group of middle-aged men and women, Dunsky et al (2017) found increased scores of attention following an aerobic exercise session on a treadmill, but not after a strength session. They also found only marginally significant improvement in executive function scores following both aerobic exercise and resistance exercise sessions.…”
Section: Figurementioning
confidence: 94%
“…For example, they provide ample evidence of specific effects of acute aerobic exercise on executive function (EF) and attention. Acute aerobic exercise is a one-session intervention, which may involve 25 min of treadmill or cycle exercise at a target heart rate of 60% of the heart rate reserve (Bullock & Giesbrecht, 2014;Dunsky et al, 2017;Netz et al, 2016;Tine, 2014;Zimmer et al, 2016). Importantly, acute aerobic exercise differs from acute resistance exercise in the immediate acute physiological responses, as well as in the long-term physiological adaptations (Knuttgen, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to aerobic exercise, recent studies have shown that a neuromotor exercise program (eg endurance training) is inversely associated with long memory performance, although aerobic exercise has greater effects on brain-derived neurotrophic growth factor (BDNF). It is extraordinarily speculated that neuromotor exercise may have a greater effect on neural survival and neurogenesis compared to the aerobic exercise program 20,21 . Therefore, both the aerobic exercise program and the Motriz, Rio Claro, v.25, Issue 4, 2019, e10190020 DOI: http://dx.doi.org /10.1590/s1980-6574201900040020 Original Article (short paper)…”
Section: Introductionmentioning
confidence: 99%
“…What has yet to be comprehensively considered, however, is the extent to which acute and/or chronic muscle strengthening activities or resistance training are associated with episodic memory performance. Notably, emerging work suggests that aerobic physical activity and resistance exercises may have unique effects on various cognitive-related variables, such as attention and executive function (Marzolini et al, 2013;Dunsky et al, 2017;Northey et al, 2017). Although speculative, aerobic-based physical activity may have greater effects on brain-derived neurotropic growth factor, whereas resistance exercise may have a greater effect on insulin-like growth factor.…”
Section: Introductionmentioning
confidence: 99%